The concepts of health and illness among young Malay breast cancer patients = Konsep kesihatan dan keuzuran dalam kalangan golongan muda pesakit barah payudara etnik Melayu - Sulaiman, Szariannie (Kolej Universiti Islam Melaka (KUIM), 2018)
Health and illness are culturally shaped concepts through which they are perceived, experienced and managed. With diverse cultural background, patients commonly bring different stories to a similar ill-health condition. Among patients suffering from chronic illness like breast cancer, understanding how these concepts are perceived is significant in managing cancer in any multi-ethnic society. In relation to this, thirteen breast cancer patients between the ages of 29 and 48 years old were selected. This study aims at exploring the meaning of health and illness as perceived by young Malay female breast cancer patients. An ethnographic fieldwork was conducted for approximately 10 months from December 2013 until October 2014in Kuala Lumpur and several areas in Selangor, Malaysia. The study employed a qualitative approach using participant observation, in-depth interviews, telephone and online interviews. It is evident in this study that informants had associated the concept of health and illness with their belief systems. For them, a good health is associated with spiritual dimension and having strong ‘semangat’. On the other hand, many of them associated illness with ‘lemah semangat’. It was observed that the concepts of health and illness among young Malay breast cancer patients are deeply rooted in their belief system, both religious and cultural beliefs.